Assessment of the thermal pyrolysis characteristics and kinetic parameters of spent coffee waste: a TGA-MS study - SAYAN, PERVİZ; POLAT, SEVGİ (TAYLOR & FRANCIS INC, 2022)
The present study aimed to investigate the pyrolysis characteristics and kinetics of spent coffee waste (SCW) at different heating rates (5-40 degrees C/min) at a temperature ranging from 30 to 800 degrees C in a thermogravimetric analyzer (TGA). First, the physicochemical properties of the SCW were characterized using X-ray diffraction, Fourier transform infrared spectrometry, scanning electron microscopy, and elemental analysis. Then, the thermal decomposition kinetic profiles were modeled using the Coats-Redfern, Flynn-Wall-Ozawa (FWO), Kissinger-Akahira-Sunose (KAS), and Starink models. All the tested models provided accurate fits of the thermogravimetric analysis data with acceptably high R-2 values. The mean activation energy of the coffee waste was 101.8, 96.7, and 97.1 kJ/mol for the FWO, KAS, and Starink models, respectively. Finally, the evolved gases detected during the decomposition by TGA coupled with a mass spectrometer (MS) primarily consisted of water, methane, and carbon dioxide.
Keywords: Spent coffee waste; pyrolysis; kinetics; gas analysis; TGA-MS; DEVOLATILIZATION KINETICS; CO-PYROLYSIS; BEHAVIOR; BIOMASS; DECOMPOSITION; RESIDUES; GROUNDS; PRETREATMENT; DEGRADATION; TOBACCO